Dinámica de crecimiento de cuatro especies forestales nativas de bosque seco, durante el período 2014 – 2021 en un huerto semillero de la Estación Experimental Zapotepamba, provincia de Loja, Ecuador - Crespo Cabrera, Luis Daniel (2024)
Dry forests occupy 42% of the surface in tropical forests worldwide; and, in Ecuador, they are found along the coast or littoral, in the provinces of Esmeraldas, Manabí, Santa Elena and Guayas; and on the south coast in the western foothills of the Andes in El Oro and Loja. Dry forests constitute an ecosystem of very high value, due to the natural dynamics they generate during rainy periods; therefore, it is essential to understand the growth dynamics of the species that make up this ecosystem. For this reason, the present research aimed to employ dendrometric and dendrochronological methods to assess the growth dynamics of four native tree species in dry forests, planted in the seed orchard of the Zapotepamba Experimental Station, during 2014-2021 period. In the year 2021, dendrometric measurements (DBH, H, G, V) were taken for the trees of the four species under study (Bursera graveolens (Kunth) Triana & Planch, Loxopterigyum huasango Spruce ex Engl, Handroanthus billbergii (Bureau & Schum.) S.O Grose, and Prosopis juliflora (Sw) DC); from which the periodic growth, annual periodic increment, and corresponding growth curves of all individuals were determined. In the same way, samples were taken with a Pressler borer for analysis, from which dendrochronological series were developed. The results showed that the species Loxopterigyum huasango reached the highest average values for the growth of the studied dendrometric variables, with a DBH of 16.902 cm; a total height of 11.684 m; a basal area of 0.029 m², and a volume of 0.251 m³; in contrast, Handroanthus billbergii exhibited the lowest growth in DBH, with 6.41 cm; Bursera graveolens showed the lowest growth in height, with 4.13 m, and in basal area, with 0.008 m²; regarding volume growth, the species Handroanthus billbergii recorded the lowest value with 0.024 m³. During the evaluation period, it was evident that the highest annual periodic increment of dendrometric variables occurred in the species Loxopterigyum huasango, with an average DBH increment of 2.817 cm/year; a total height increment of 1.947 m/year; a basal area increment of 0.0048 m²/year, and a volume increment of 0.041 m³/year; in contrast, Handroanthus billbergii was the species with the lowest growth in DBH, with 1.06 cm/year, and basal area with 0.0009 m²/year; meanwhile, Bursera graveolens exhibited the lowest height growth, with 0.68 m/year, and volume growth of 0.024 m³/year. The dendrochronological analysis revealed that the species Loxopterigyum huasango had the highest cumulative growth between 2014 and 2021, with an accumulated growth of 81.89 mm; Prosopis juliflora followed with an accumulated value of 48.65 mm; while Handroanthus billbergii was the forest tree species with the lowest cumulative growth in diameter, with 28.205 mm; regarding the results of the annual periodic growth in diameter, it was found that Loxopterigyum huasango, had an average annual growth of 9.10 mm; followed 5 by Bursera graveolens with 4.68 mm; Prosopis juliflora with 4.37 mm; and finally, Handroanthus billbergii with 3.71 mm